THE ROLE OF ICE BREAKING IN SHAPING THE LEARNING ENVIRONMENT AND ENHANCING PARTICIPANT SATISFACTION - Pratiwi Pratiwi (Bisnis Event, 2026)
This study investigates the influence of ice-breaking activities on the learning environment and participant satisfaction in community-based training programmes, particularly those linked to educational events in the MICE sector. Even though ice breaking is used a lot, there are not much empirical evidence about how it affects training outcomes. This research examines the direct effects of ice breaking on the learning environment, its impact on participant satisfaction, and the mediating role of the learning environment. A quantitative explanatory design was employed, involving 158 participants who participated in organised nonformal training sessions organised by the Institut Pariwisata Tedja Indonesia in 2025. Data were gathered by a 24-item questionnaire and evaluated using PLS-SEM with SmartPLS, encompassing assessments of convergent validity, discriminant validity, and reliability. Results indicate that ice breaking markedly enhances the learning environment (β = 0.783, p < 0.001). The learning environment has a big effect on the link between ice breaking and how happy participants are (β = 0.573, p < 0.001). A significant albeit modest direct effect of ice breaking on satisfaction was seen (β = 0.191, p = 0.003). The results show that well-structured opening activities improve psychological readiness, engagement, and positive emotional states, which in turn improve the overall training experience for participants. The study contributes to the literature on experiential learning and offers practical guidance for facilitators and event organisers to develop more engaging and effective training programmes.